A Network Theory View on the Thalamo-Cortical Loop - Bakouie, F.; Gharibzadeh, S.; Towhidkhah, F. (Нейрофизиология, 2014)
We used a network theory approach, based on the dynamic core hypothesis (DCH), to study the thalamo-cortical loop (TCL) and its subsets regarding their role in consciousness. We used the Collation of Connectivity Data on the Macaque Brain (CoCoMac) and calculated the degree distributions, transmission coefficients, connection density, clustering coefficients, path lengths, and modularity. Our results showed that the TCL and cortex exhibit exponential degree distributions, and the ratio of efferent/afferent connections in the thalamus is smaller than 1.0 This may support the notion that the connections received by the thalamus from the cortex play a key role in improving information processing in the conscious states. The average values of transmission coefficients for the cortex and TCL were found to be equal to 1.49 and 1.28, respectively. This indicates that: (i) the cortex is a system that mainly transmits information outward rather than receives it; (ii) the TCL is a cooperative system that performs this in a give-and-take manner; (iii) connections of the cortex are denser than those in the TCL, showing that the cortex might be advantageous for processing of complicated information during consciousness; (iv) both the TCL and cortex are small-world systems; (v) the scaled value of the characteristic path length in the TCL is smaller than that in the cortex, which implies a higher speed potential for information processing in the TCL than in the cortex; (vi) the scaled value of the clustering coefficient is nearly the same in the cortex and TCL, and (vii) the number of modules is 5 in the cortex and 6 in the TCL.